The Relationship Between The Level of Mother’s Breastfeeding Knowledge With Exclusive Breastfeeding Practice in The Center of Public Health Kenjeran - Husnayain, Zida Shofy; Nurida, Annisa; Marlina, Uning; Prahasanti, Kartika (Universitas Muhammadiyah Semarang, 2021)
Background: Exclusive breastfeeding is giving breast milk exclusively from newborns to 6 months of age without giving any food. Exclusive breastfeeding is essential for optimal baby growth and development, contains various essential nutrients for babies. In 2018 the coverage of exclusive breastfeeding in Indonesia still reached 65.16%, and the coverage of breastfeeding in East Java itself was still below the target of 76.98%. The low level of exclusive breastfeeding is still a problem because it can cause the baby's immune system to become lower, indigestion and illness risk in the baby is more generous to target.Objective: To determine the relationship between mothers' level of knowledge about breastfeeding and exclusive breastfeeding at Kenjeran Primary Health Center.Methods: This observational analytic study with a cross-sectional study design. The sampling technique was using the purposive sampling technique. Respondents in this study were mothers who had babies 6-24 months. The data collection process was directly asked through a questionnaire and analyzed using the contingency coefficient test.Results: This study involved 51 mothers who gave exclusive breastfeeding and 51 mothers who did not. The results showed that most of the respondents who breastfed and did not have the right knowledge level. Based on the contingency coefficient test results, it was found that there was no relationship between the level of mother's knowledge about breast milk to give exclusive breastfeeding at the Kenjeran Primary Health Center (the value of p = 0.251).Conclusion: There is no relationship between mothers' level of knowledge about breastfeeding and exclusive breastfeeding at the Kenjeran Primary Health Center.